NOTES ON THE FRIGAT-E MACKERELS, AUXIS THAZARD (LACEPEDE) AND A, TAPEINOSOMA BLEEKER, FROM INDIAN WATERS - Jones, S. (Indian Journal of Fisheries, 2015)
The so-called frigate mackerels of the genus Auxis are the smallest of the tunas and could be distinguished from aU other genera of the family Thunnidae by the wide interspace (nearly equal to the length of the head) between the first and the second dorsal. Another distinguishing character is the size of the axillary scales (between the ventral fins) which are equal in length to the fins in Auxis while in other Thunnidae they are only about one-half in length. In addition to the geno-type, Auxis (hazard (Scomber thazard Lacdp6de), which is a widely distributed fish found in all the warm seas, a few species have been described which according to some are only synonyms of the above. Recently Wade (1949) has shown that two spedes, viz., Auxis (hazard and A. (apeinosoma, occur in the Philippine waters thereby helping to establish the validity of the second species. It has been possible to obtain recently both the species from the Indian waters and notes on them are given in this article as there are no previous published records of these from India.